Perbedaan Antara Status Gizi Dan Kejadian Penyakit Ispa Pada Balita Imunisasi Lengkap Dan Balita Imunisasi Tidak Lengkap Di Wilayah Kerja Puskesmas Polokarto Sukoharjo - Ningsih, Sri Dian; , Luluk Ria Rakhma, S.Gz., M.Gizi; , Tri Wibowo Anang.SB; S.KM., M.Gizi (2017)
Immunization is disease prevention efforts to reduce morbidity, disability and death from diseases that can be prevented by immunization. One of them is the ARI (Acute Respiratory Infections) will occur when the body's immune decline so that the efforts made among others by providing a complete basic immunization. This type of research is observational analytic with cross sectional approach by the number of respondents 66 people were obtained by simple random sampling technique. Immunization data obtained through observation KIA book while the nutritional status obtained by the measurement of weight and height directly and ARI obtained through a questionnaire. Statistical analysis using Independent T-test. Results of the study were mostly normal nutritional status at full immunization group was 72.7%. While infants are not exposed to the highest in the group of infants ISPA complete immunization is 60.6%. The results of the bivariate analysis showed no significant difference between immunization against ARI (p = 0.62), but no difference between immunization status on nutritional status (p = 0.23).